Lateral fricatives and lateral emphatics in southern Saudi Arabia and Mehri - Watson, Janet C.E. (Proceedings of the Seminar for Arabian Studies, 2011)
Arabic was traditionally described as lughat al-ḍād ’the language of ḍād’ due to the perceived unusualness of the sound. From Sībawayhi’s description, early Arabic ḍād was clearly a lateral or lateralized emphatic. Lateral fricatives are assumed to have formed part of the phoneme inventory of Proto-Semitic, and are attested in Modern South Arabian languages (MSAL) today. In Arabic, a lateral realization of ḍād continues to be attested in some recitations of the Qurʿān. For Arabic, the lateral ḍād described by Sībawayhi was believed to be confined to dialects spoken in Ḥḍadramawt. Recent fieldwork by Asiri and al-Azraqi, however, has identified lateral and lateralized emphatics in dialects of southern ʿAsīr and the Saudi Tihāmah. These sounds differ across the varieties, both in their phonation (voicing) and manner of articulation — sonorants and voiced and voiceless fricatives — in their degree of laterality, and in their phonological behaviour: the lateralized ḍād in the southern Yemeni dialect of Ghaylḥabbān, for example, has a non-lateralized allophone in the environment of/r/or /l/. Recent phonetic work conducted by Watson on the Modern South Arabian language, Mehri, shows a similar range of cross-dialect variety in the realization of the lateral(ized) emphatic. In this paper, we discuss different reflexes of lateral(ized) emphatics in four dialects of the Saudi Tihāmah; we show that some of these dialects contrast cognates of *ḍ and *[symbol]; and we show that lateral emphatics attested in dialects of the Modern South Arabian language, Mehri, spoken in areas considerably to the south of the Saudi Tihāmah, show a similar degree of variation to that of the Arabic dialects of the Saudi Tihāmah.